Desorption of VOC from polymer adsorbent in multistage fluidized bed - Zheng, Jiale; Song, Wenli; Du, Lin; Wang, Lina; Li, Songgeng (Chinese journal of chemical engineering, 2020)
The desorption process of volatile organic compounds (VOC) from a polymer adsorbent in counter-current multistage fluidized bed was studied. And a mathematical model considering the mass transfer dynamics was developed, which was validated from experiment data. The gaseous ethyl acetate mass transfer was discussed, and the limiting step is the intraparticle mass transfer of the desorption process. The value of intraparticle mass transfer coefficient is between 1.85 × 10−6 and 1.38 × 10−5 m·s−1 under temperature of 100–160 °C. Experiments under different operating conditions were carried out. The effects of operating conditions such as gas–solid flow ratio, gas inlet temperature and total stage number of multistage fluidized bed on outlet VOCs concentration and desorption efficiency were discussed. The maximum outlet VOCs concentration and corresponding desorption efficiency of the multistage fluidized bed desorber was calculated under different gas inlet temperatures and total stage numbers. [Display omitted] •The desorption of VOC from adsorbent in counter-current multistage fluidized bed is studied•The intraparticle mass transfer process is the limiting step of desorption process•There is a maximum outlet VOC concentration for different operating conditions•The desorption efficiency increases with the increase of gas–solid flow ratio, gas inlet temperature and total stage number